2016
DOI: 10.1016/j.phrs.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa (black seed) effects on plasma lipid concentrations in humans: A systematic review and meta-analysis of randomized placebo-controlled trials

Abstract: The effects of Nigella sativa (NS) on plasma lipid concentrations are controversial. A systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to obtain a conclusive result in humans. PubMed-Medline, SCOPUS, Web of Science, and Google Scholar databases were searched (up to August 2015) to identify RCTs investigating the impact of NS on total cholesterol, LDL-cholesterol (LDL-C), HDL-cholesterol (HDL-C), and triglycerides concentrations. A random-effects model and the generic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 75 publications
(141 reference statements)
6
53
0
1
Order By: Relevance
“…These alterations suggest the importance of tiger nut oil‐based diet in the management or prevention of cardiovascular related disorder. This is consistent with previous studies demonstrating the importance of other seed and nut oil (Al‐Naqeep et al, ; Gossell‐Williams et al, ; Sahebkar et al, ). The elevated level of HDLc could lower predisposition to atherosclerosis and cardiovascular diseases (Chen et al, ).…”
Section: Resultssupporting
confidence: 93%
“…These alterations suggest the importance of tiger nut oil‐based diet in the management or prevention of cardiovascular related disorder. This is consistent with previous studies demonstrating the importance of other seed and nut oil (Al‐Naqeep et al, ; Gossell‐Williams et al, ; Sahebkar et al, ). The elevated level of HDLc could lower predisposition to atherosclerosis and cardiovascular diseases (Chen et al, ).…”
Section: Resultssupporting
confidence: 93%
“…Unlike pervasive evidence for the effects of NS use on the lipid profile, the administration of powdered NS seeds was reported to have had no significant effect on BP, serum lipid levels, blood sugar, or body weight in adults [73]. According to some meta-analyses, overall, the use of NS was shown to reduce the plasma levels of TC, LDL-C and TG, but its effect on HDL-C was not significant [74, 75]. Whereas the use of NS seed oil was observed to have greater effects on the serum TC and the LDL-C levels, versus the use of seed powder, elevation of the HDL-C levels was found only after supplementation with NS seed powder [75].…”
Section: Resultsmentioning
confidence: 99%
“…According to some meta-analyses, overall, the use of NS was shown to reduce the plasma levels of TC, LDL-C and TG, but its effect on HDL-C was not significant [74, 75]. Whereas the use of NS seed oil was observed to have greater effects on the serum TC and the LDL-C levels, versus the use of seed powder, elevation of the HDL-C levels was found only after supplementation with NS seed powder [75]. …”
Section: Resultsmentioning
confidence: 99%
“…sativa powder (14.72 and 7.49, respectively) but on the contrary of FPG, powder had greater lowering effect on PPBG compared with oil (18.26 and 12.87, respectively). Other meta‐analysis that investigates different effect of oil and powder supplements also has been reported that oil supplement were more effective in lowering low‐density lipoprotein and cholesterol (Sahebkar, Beccuti, et al, ). However, N .…”
Section: Discussionmentioning
confidence: 99%